Police perceptions of human trafficking in South Africa - Morero, Motseki (Technium Social Sciences Journal, 2022)
Human trafficking is perceived to be a serious and growing problem worldwide. Yet for many years, society as a whole, and the policing profession in particular in South Africa, did not fully grasp the scale and complexity of the problem or its impact. The article seek to understand and determine the perceptions of police regarding human trafficking in South Africa. The study followed a qualitative approach and purposive sampling was used to select 28 participants in three selected areas of Gauteng Province. The findings revealed that the police lack intensive training on issues of human trafficking and further revealed that police were not able to differentiate between the victims of human trafficking and prostitution. The police should be given adequate time, funding, and training needed to establish a wide base of experience and knowledge from which they can draw upon for future human trafficking investigation.